Evaluation of radiochemical purities of some radiopharmaceuticals in Shiraz Namazi teaching hospital - Hossein Sadeghpour; Mehrosadat Alavi; Majid Shahedi; Seyed Mohammad Entezarmahdi; Amirhossein Sakhteman (Shiraz University of Medical Sciences, 2015)
Many radiopharmaceuticals, as a special group of drugs, are eventually prepared at the nuclear medicine departments of the hospitals. Therefore, their quality control procedures such as sterility tests, radionuclide, radiochemical and chemical purity should be carried out in the hospitals. In this study, radiochemical purity for more than 300 preparations of three different radiopharmaceutical formulations from commercial kits were tested using instant thin layer chromatography. The formulations 99mTc-DTPA, 99mTc-MDP and 99mTc-MIBI were obtained from Pars Isotope Co. Several paper chromatographic systems including standard and factory recommended thin layer chromatography systems were used in this study. In addition different equipments for detection of radioactivity in paper chromatography like gamma camera and dose calibrator were used. The results showed that the most observed impurities were hydrolyzed reduced technetium (HR-Tc). There were no significant differences between calculated 99mTc-MIBI radiochemical purities when the radioactive detection device was gamma camera instead of dose calibrator. In case of 99mTc-DTPA and 99mTc-MDP, there were significant differences in detection of HR-Tc. On the contrary, no significant differences in free pertechnetate were observed when package insert procedures for quality control were used instead of those recommended in the references. Finally, we observed that the package insert procedures for quality control can offer higher radiochemical purities.